Decreased HDL-C Levels as a Predictor of Organ Failure in Acute Pancreatitis in the Emergency Department - Ana Rocío Venegas-Tamayo; Olga Mariel Peña-Veites; Martha Alicia Hernández-González; Cornelio Barrientos-Alvarado (Life, 2023)
High-density lipoprotein cholesterol (HDL-C) is reported as a biomarker of systemic inflammation and multi-organ failure (MOF), which has been rarely investigated in acute pancreatitis (AP), a frequent condition in the emergency department (ED). The objective was to study the predictive capacity of the decrease in HDL-C to the progression of MOF in AP in the ED; analyzing 114 patients with AP for one year in a longitudinal and prospective study, AP severity was obtained by the Atlanta classification, in relation to modified Marshall and Bedside Index for Severity in Acute Pancreatitis (BISAP) scores, and clinical and laboratory parameters in a 48 h hospital stay. The area under the receiver operating characteristic (ROC) curve was used to estimate the validity of the predictor and define optimal cut-off points. It was found that AP was classified as severe in 24.5%, mainly for biliary etiology (78.9%) and female sex (73.6%). As a biomarker, HDL-C decreased from 31.6 to 29.5 mg/dL in a 48 h stay (p < 0.001), correlating negatively with the increase in severity index > 2 and the modified Marshall (p < 0.032) and BISAP (p < 0.009) scores, finding an area under the ROC curve with a predictive capacity of 0.756 (95% CI, 0.614–0.898; p < 0.004) and a cut-off point of 28.5 mg/dL (sensitivity: 79%, specificity: 78%), demonstrating that the decrease in HDL-C levels serves as a useful indicator with a predictive capacity for MOF in mild to severe AP, during a 48 h hospital stay in the ED.